SUSTAINABLE TOURISM MANAGEMENT BASED ON TRI HITA KARANA IN THE SANGEH TOURIST ATTRACTION AREA - Rediyasa, Ketut; Wibie Verdian; I Nengah Darma Yasa (UHN IGB Sugriwa Denpasar, 2026)
This research aims to explore the implementation of the Tri Hita Karana concept in developing sustainable tourism at the Sangeh Tourism Object, Bali. Through a qualitative approach, data was collected through interviews with tourism managers, participant observation, and analysis of related documents. The findings show that the Tri Hita Karana concept has become an important basis in tourism management and development in Sangeh, with an emphasis on the balance between the relationship between humans and God, humans and humans, and humans and nature. However, research also identifies a number of challenges, including conflicts of interest, socioeconomic changes, and environmental pressures. However, active participation of local communities, environmental protection efforts, and cultural education initiatives have become important strategies in improving the sustainability of tourism in Sangeh. Based on these findings, recommendations are proposed to strengthen the implementation of Tri Hita Karana, expand community participation, and strengthen sustainable tourism practices in this destination.